Semi-aromatic polyamide material as well as preparation method and application thereof

By adding second polyamide and polyvinylpyrrolidone to the semiaromatic polyamide material, and adding high benzene ring content and appropriate amount of flame retardant, the heat dissipation and laser welding problems of new energy vehicle materials under high current and voltage are solved, and high light transmittance, flame retardancy, welding strength and solvent resistance are achieved.

CN119708833AActive Publication Date: 2025-03-28SHANGHAI KINGFA SCI & TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411808673.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-28
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The high current and voltage of new energy vehicles lead to an increase in heat generation, requiring higher heat dissipation capabilities. Traditional water cooling media cannot meet the requirements. As a replacement medium, ethylene glycol/water solution requires materials to have high solvent resistance. At the same time, the materials need to have high light transmittance, flame retardancy and welding strength during laser welding.

Method used

Using a semiaromatic polyamide material, by adding a second polyamide and polyvinylpyrrolidone to the first polyamide, the hydrogen bond is destroyed and amide exchange is carried out, the light transmittance and welding strength of the material are improved, and flame retardant and solvent resistance are achieved through the addition of high benzene ring content and appropriate amount of flame retardant.

Benefits of technology

It realizes the high light transmittance, flame retardancy, welding strength and solvent resistance of the material, meeting the high requirements of new energy vehicles for thermal management systems and battery systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005179967730000111
    Figure BDA0005179967730000111
  • Figure BDA0005179967730000121
    Figure BDA0005179967730000121
  • Figure BDA0005179967730000122
    Figure BDA0005179967730000122
Patent Text Reader

Abstract

The invention provides a semi-aromatic polyamide material as well as a preparation method and application thereof, and belongs to the technical field of high polymer materials. The semi-aromatic polyamide material disclosed by the invention is prepared from the following components in parts by weight: 45 to 62 parts of first polyamide, 5 to 10 parts of second polyamide, 3 to 5 parts of polyvinylpyrrolidone, 10 to 12 parts of flame retardant and 20 to 30 parts of filler. According to the semi-aromatic polyamide material, the second polyamide and the polyvinylpyrrolidone are added into the first polyamide, hydrogen bonds of the first polyamide and the second polyamide are destroyed through the polyvinylpyrrolidone, so that the first polyamide and the second polyamide are subjected to amide exchange, and the semi-aromatic polyamide material has good light transmittance, welding strength and solvent resistance at the same time; besides, the content of benzene rings in the semi-aromatic polyamide is high, flame retardance can be realized under the condition that a small amount of flame retardant is added, and the semi-aromatic polyamide material with high flame retardance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of polymer materials, and in particular to a semi-aromatic polyamide material and a preparation method and application thereof. Background Art

[0002] At present, due to the increase in current and voltage values, the overall heat generation of new energy vehicles has increased significantly, so higher heat dissipation requirements are put forward for the thermal management system and battery system. Based on the above reasons, the thermal management system no longer uses traditional water as a cooling medium, but uses ethylene glycol / water solution as a cooling medium. However, ethylene glycol has very high requirements for the solvent resistance of the material. After using it for 96 hours in the ethylene glycol heating state, the mechanical properties of the PA66 material will decay to less than 50% after 96 hours of use; at the same time, due to the requirements of processing efficiency and airtightness, the materials used in the thermal management system and the battery system are connected by laser welding. Laser welding has extremely high requirements for the light transmittance of the material. Some solvent-resistant materials such as polyphenylene sulfide have poor light transmittance, and the performance of laser welding itself is extremely poor, and the welding strength and airtightness strength cannot be guaranteed; new energy vehicles are currently more sensitive to ignition and fire, so flame retardant requirements are put forward for materials, and the addition of flame retardants will further reduce the light transmittance of the material, making it impossible to guarantee welding of the material.

[0003] Therefore, there is an urgent need for a material with high solvent resistance, light transmittance, flame retardancy and laser welding strength. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and to provide a semi-aromatic polyamide material having solvent resistance, light transmittance, flame retardancy and high laser welding strength, as well as a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose, the technical solution adopted by the present disclosure is as follows: In the first aspect, a semi-aromatic polyamide material is provided, comprising the following components in parts by weight: 45-62 parts of a first polyamide, 5-10 parts of a second polyamide, 3-5 parts of polyvinyl pyrrolidone, 10-12 parts of a flame retardant, and 20-30 parts of a filler;

[0006] Wherein, the first polyamide and the second polyamide are copolymers of dicarboxylic acid and hexamethylenediamine, and the dicarboxylic acid is terephthalic acid and isophthalic acid;

[0007] The first polyamide comprises repeating units derived from: 60-70% by mole of terephthalic acid, 30-40% by mole of isophthalic acid, based on the sum of the molar contents of the dicarboxylic acids being 100%;

[0008] The second polyamide comprises repeating units derived from 30-40% by mole of terephthalic acid, 60-70% by mole of isophthalic acid.

[0009] In some embodiments, the molar content of terephthalic acid in the first polyamide is 65-70%.

[0010] In some embodiments, the weight portion of the second polyamide is 6.5-8 parts.

[0011] In some embodiments, the flame retardant is aluminum diethylphosphinate.

[0012] In some embodiments, the filler is at least one of a fibrous filler and a non-fibrous filler; the fibrous filler is selected from at least one of glass fiber, carbon fiber, and organic fiber, and the non-fibrous filler is selected from at least one of a granular filler, a layered filler, and a nanofiller.

[0013] In some embodiments, the semi-aromatic polyamide material further comprises 1-3 parts by weight of a processing aid; the processing aid comprises at least one of a heat stabilizer, an antioxidant, a nucleating agent, an antistatic agent, a foaming agent, a lubricant, a plasticizer, a release agent, and a pigment.

[0014] In a second aspect, a method for preparing the semi-aromatic polyamide material is provided, comprising the following steps: mixing the components uniformly in proportion, and then performing melt extrusion granulation to obtain the semi-aromatic polyamide material.

[0015] In some embodiments, the temperature of the melt extrusion granulation is 290-340°C.

[0016] In a third aspect, a use of the semi-aromatic polyamide material in the preparation of laser welding parts is provided.

[0017] In a fourth aspect, a laser welding component is provided, wherein the laser welding component comprises the semi-aromatic polyamide material.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adds a second polyamide and polyvinyl pyrrolidone to the first polyamide, destroys the hydrogen bonds between the first polyamide and the second polyamide through the polyvinyl pyrrolidone, causes the first polyamide and the second polyamide to undergo amide exchange, and enables the semi-aromatic polyamide material to have good light transmittance, welding strength and solvent resistance at the same time; in addition, the semi-aromatic polyamide has a high benzene ring content, and can achieve flame retardancy by adding a small amount of flame retardant, thereby obtaining a semi-aromatic polyamide material with high flame retardancy. DETAILED DESCRIPTION

[0019] In order to facilitate understanding of the present disclosure, the present disclosure will be described more fully below. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present disclosure more thorough and comprehensive.

[0020] As used herein:

[0021] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0022] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0023] When amount, concentration or other value or parameter is represented by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when disclosing range "1-5", described range should be interpreted as including range "1-4", "1-3", "1-2", "1-2 and 4-5", "1-3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the range is intended to include its end value and all integers and fractions within the range.

[0024] In these examples, parts and percentages are by mass unless otherwise indicated.

[0025] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0026] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0027] In a first aspect, the present disclosure provides a semi-aromatic polyamide material, comprising the following components in parts by weight: 45-62 parts of a first polyamide, 5-10 parts of a second polyamide, 3-5 parts of polyvinyl pyrrolidone, 10-12 parts of a flame retardant, and 20-30 parts of a filler;

[0028] Wherein, the first polyamide (PA6T / 6I) and the second polyamide (PA6I / 6T) are copolymers of dicarboxylic acid and hexamethylenediamine, and the dicarboxylic acid is terephthalic acid and isophthalic acid;

[0029] The first polyamide comprises repeating units derived from 60-70% terephthalic acid and 30-40% isophthalic acid, based on 100% of the total molar content of dicarboxylic acids; the second polyamide comprises repeating units derived from 30-40% terephthalic acid and 60-70% isophthalic acid.

[0030] The present invention discloses adding a second polyamide and polyvinyl pyrrolidone to a first polyamide, destroying the hydrogen bonds between the first polyamide and the second polyamide through the polyvinyl pyrrolidone, causing the first polyamide and the second polyamide to undergo amide exchange, so that the semi-aromatic polyamide material has good light transmittance, welding strength and solvent resistance at the same time; in addition, the semi-aromatic polyamide has a high benzene ring content and can achieve flame retardancy by adding a small amount of flame retardant, thereby obtaining a semi-aromatic polyamide material with high flame retardancy.

[0031] Specifically, the weight parts of the first polyamide can be, but are not limited to, 45 parts, 48 ​​parts, 50 parts, 52 parts, 54 parts, 56 parts, 58 parts, 60 parts, and 62 parts;

[0032] Specifically, the weight proportion of the second polyamide may be, but is not limited to, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts; preferably, it is 6.5-8 parts.

[0033] Specifically, the weight parts of the polyvinyl pyrrolidone can be, but are not limited to, 3 parts, 3.2 parts, 3.5 parts, 3.7 parts, 4 parts, 4.3 parts, 4.5 parts, 4.8 parts, and 5 parts;

[0034] Specifically, the weight parts of the flame retardant can be, but are not limited to, 10 parts, 10.2 parts, 10.5 parts, 10.7 parts, 11 parts, 11.3 parts, 11.8 parts, and 12 parts;

[0035] Specifically, the weight proportion of the filler may be, but is not limited to, 20 parts, 22 parts, 24 parts, 26 parts, 28 parts, or 30 parts.

[0036] Specifically, based on the total molar content of dicarboxylic acids as 100%, the molar content of terephthalic acid in the first polyamide can be but not limited to 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%; preferably 65-70%; the molar content of isophthalic acid can be but not limited to 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%.

[0037] Specifically, based on the total molar content of dicarboxylic acids as 100%, the molar content of terephthalic acid in the second polyamide can be but not limited to 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%; the molar content of isophthalic acid can be but not limited to 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%.

[0038] Specifically, in the present disclosure, the molar contents of terephthalic acid and isophthalic acid in the first polyamide and the second polyamide will affect the performance of the semi-aromatic polyamide material. If the molar content of terephthalic acid in the first polyamide is lower than 60%, the solvent resistance of the semi-aromatic polyamide material will be significantly reduced; if the molar content of terephthalic acid in the second polyamide is higher than 40%, the solvent resistance of the semi-aromatic polyamide material will be significantly reduced; the present disclosure preferably has a molar content of terephthalic acid in the first polyamide of 65-70% to obtain a semi-aromatic polyamide material with high light transmittance, flame retardancy, laser welding strength and solvent resistance.

[0039] Specifically, the weight of the second polyamide is also one of the factors affecting the performance of the semi-aromatic polyamide material. If the weight of the second polyamide is too low, the light transmittance and laser welding strength of the semi-aromatic polyamide material will be reduced; if the weight of the second polyamide is too high, the solvent resistance of the semi-aromatic polyamide material will be reduced.

[0040] Specifically, based on the mass percentage of the polyamide material as 100%, the total mass percentage of the first polyamide and the second polyamide is not less than 35%; preferably, the total mass percentage of the first polyamide and the second polyamide is not less than 40%, and more preferably, the total mass percentage of the first polyamide and the second polyamide is not less than 45%.

[0041] Specifically, the first polyamide and the second polyamide can be capped with an end-capping agent, and the end-capping agent can react with the end of the chain segment of the first polyamide or the second polyamide during the polymerization process to achieve other purposes of controlling the molecular weight of the first polyamide or the second polyamide or changing the type or activity of the end group, and the end-capping agent is selected from a carboxylic acid containing only one reactive carboxyl group. The "containing only one reactive carboxyl group" should be understood as the carboxylic acid as the end-capping agent, and its structure can contain one, two or more carboxyl groups and / or other derivative functional groups, but only one of them has the activity to react with the end of the polyamide chain growth.

[0042] The carboxylic acid end-capping agent is preferably but not limited to at least one of acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, octanoic acid, dodecanoic acid, stearic acid, cyclohexanoic acid, and benzoic acid.

[0043] The content of the carboxylic acid end-capping agent is not less than 0.1 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide; preferably, the content of the carboxylic acid end-capping agent is not less than 0.5 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide; more preferably, the content of the carboxylic acid end-capping agent is not less than 0.8 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide; particularly preferably, the content of the carboxylic acid end-capping agent is not less than 1.0 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide; usually In some embodiments, the content of the carboxylic acid end-capping agent is not higher than 6.0 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide; preferably, the content of the carboxylic acid end-capping agent is not higher than 5.8 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide; more preferably, the content of the carboxylic acid end-capping agent is not higher than 5.5 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide; particularly preferably, the content of the carboxylic acid end-capping agent is not higher than 5.0 mol / % based on the total amount of dicarboxylic acid reaction monomers constituting the first polyamide or the second polyamide.

[0044] The first polyamide or the second polyamide is manufactured by a melt polymerization method, for example, a polymerization method in which a solution containing a dicarboxylic acid and hexamethylenediamine is continuously removed from the solution water and the condensation product water under an environment of increasing temperature and pressure; or hexamethylenediamine can be added to the dicarboxylic acid in a molten state for polycondensation. In order to maintain a uniform liquid phase, it is preferable to gradually and continuously add hexamethylenediamine to the molten dicarboxylic acid. During the polymerization reaction, the temperature is continuously increased and adjusted so that the temperature is not lower than the melting point of the polyamide oligomer and the polyamide product to carry out polycondensation.

[0045] Specifically, the preparation method of the first polyamide or the second polyamide comprises the following steps:

[0046] Hexamethylenediamine, terephthalic acid, isophthalic acid, a capping agent and deionized water are added into a reactor with a nitrogen atmosphere and a pressure of 2.5-3Mpa, the reactor is heated to 160-200°C for reaction for 0.5-1.5h, and then the temperature is further raised to 220-240°C for reaction for 10-15h to obtain the first polyamide or the second polyamide.

[0047] Specifically, the viscosity value of the first polyamide or the second polyamide is independently 1.8-2.4, for example, it can be but not limited to 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4; the test method is ISO307:2019, and the test solvent is sulfuric acid.

[0048] In some embodiments, the flame retardant is aluminum diethylphosphinate.

[0049] Specifically, the K value of the polyvinyl pyrrolidone is 10-120, for example, it can be but not limited to 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120.

[0050] In some embodiments, the filler is at least one of a fibrous filler and a non-fibrous filler; the fibrous filler is selected from at least one of glass fiber, carbon fiber, and organic fiber, and the non-fibrous filler is selected from at least one of a granular filler, a layered filler, and a nanofiller.

[0051] Specifically, the filler is glass fiber; the composition of the glass fiber can be formed using A-glass, C-glass, D-glass, E-glass, M-glass, R-glass, S-glass or a mixture thereof, preferably E-glass.

[0052] Specifically, the glass fiber can be selected from different forms, suitable forms include continuous glass fiber, chopped glass fiber (cut into a size of 1-10 mm) and finely ground glass fiber (ground into a size of 10-500 μm), and different forms of glass fiber can be mixed and used.

[0053] Specifically, the glass fiber can be selected from different cross-sectional shapes, preferably but not limited to circular, elliptical, and quasi-rectangular cross-sectional shapes, more preferably non-circular cross-sectional shapes, and particularly preferably quasi-rectangular cross-sectional shapes. The described quasi-rectangular shape should be understood as having a general shape similar to a rectangle, and the main variants included are that the right angles of the rectangle are changed to rounded corners with a certain curvature. The reciprocal of the curvature is not greater than 50% of the long diameter of the quasi-rectangle, preferably, the reciprocal of the curvature is not greater than 25% of the long diameter of the quasi-rectangle; more preferably, the reciprocal of the curvature is not greater than 10% of the long diameter of the quasi-rectangle; particularly preferably, the reciprocal of the curvature is not greater than 12.5% ​​of the long diameter of the quasi-rectangle; at the same time, the reciprocal of the curvature is not less than 8% of the short diameter of the quasi-rectangle; preferably, the reciprocal of the curvature is not less than 12.5% ​​of the short diameter of the quasi-rectangle; more preferably, the reciprocal of the curvature is not less than 25% of the short diameter of the quasi-rectangle; particularly preferably, the reciprocal of the curvature is not less than 40% of the short diameter of the quasi-rectangle. According to a preferred embodiment, the glass fiber has a pseudo-rectangular cross-section with a long diameter / short diameter ratio of 1.5-10; preferably, the long diameter / short diameter ratio is 2.5-8; more preferably, the long diameter / short diameter ratio is 2.5-5.

[0054] Specifically, the polyamide material of the present invention contains not less than 20% by weight of glass fiber; preferably, it contains not less than 25% by weight of glass fiber; at the same time, the polyamide material of the present invention contains not more than 65% by weight of glass fiber; preferably, the polyamide material of the present invention contains not more than 60% by weight of glass fiber; more preferably, the polyamide material of the present invention contains not more than 55% by weight of glass fiber.

[0055] The glass fibers contained in the polyamide material disclosed herein can be one, two or more in composition, form and cross-sectional morphology. When there are two or more glass fibers, the total content of the glass fibers still applies to the above range.

[0056] In some embodiments, the polyamide material further comprises 1-3 parts by weight of a processing aid; the processing aid comprises at least one of a heat stabilizer, an antioxidant, a nucleating agent, an antistatic agent, a foaming agent, a lubricant, a plasticizer, a release agent, and a pigment. Preferably, the polyamide material of the present disclosure does not comprise a processing aid.

[0057] The production method of the polyamide composite with improved laser weldability of the present invention is not particularly strictly limited, and is carried out using a blending device such as an internal mixer, a single screw or a twin screw extruder. The order of adding the components is not particularly strictly limited, and they can be added simultaneously or in a certain order. Two or more components can be selected from all the components for pre-mixing or internal mixing. For example, the laser-transmitting colorant can be pre-formed into a masterbatch, and then added to the melt of other components in the form of a masterbatch in a set ratio for extrusion. Under the condition that the mixing capacity of the equipment allows, the particles formed by the masterbatch and other components can also be mixed and melt-processed in a set ratio when molding or producing parts. The thermoplastic resin used in the masterbatch can be the polyamide resin described in the present invention, or it can be other polyamide resins, preferably PA6, PA66. In order to overcome the loss of glass fiber and flame retardant during the extrusion process, it is preferred to add them in a set ratio in the middle of the extrusion equipment after the other components are fully melted.

[0058] Specifically, the preparation method of the semi-aromatic polyamide material comprises the following steps:

[0059] After the first polyamide, the second polyamide and polyvinyl pyrrolidone are uniformly mixed, the resulting mixture is added to the main feeding system of the extruder for melt mixing, the flame retardant is added to the first side feeding system of the extruder, the glass fiber is added to the second side feeding system of the extruder, and the mixture is extruded and granulated to obtain a semi-aromatic polyamide material.

[0060] In some embodiments, the temperature of the melt extrusion granulation is 290-340°C; for example, it can be but not limited to 290°C, 295°C, 300°C, 310°C, 320°C, 325°C, 330°C, 335°C, 340°C.

[0061] In a third aspect, the application of the polyamide material in the preparation of laser welding parts is provided.

[0062] In a fourth aspect, a laser welding component is provided, wherein the laser welding component comprises the polyamide material.

[0063] The laser welding parts include the polyamide material (i.e., laser-transmitting resin material) and another laser-absorbing resin material, and the laser is irradiated through the transmissive resin material to the absorbent resin material attached thereto, and the laser energy accumulated on the contact surface of the absorbent resin material heats and melts the contact area. The transmissive resin material is also heated / melted by heat transfer, so that the resin materials are easily and firmly combined together. The laser can directly irradiate the welding area or can be guided to the contact area using an optical device such as a mirror or optical fiber. These and other techniques can be appropriately adopted according to individual welding operations and selected by those skilled in the art. If necessary, pressure can be further applied to the bonding surface.

[0064] The laser absorbing resin may be polyamide resin, polyester resin, polycarbonate resin, polyolefin resin, styrene-based resin, polyphenylene ether resin, polyethylene-based resin, acrylic resin, acetal resin, etc. In order to form stronger welding performance and consider the influence of compatibility, the laser absorbing resin is polyamide resin.

[0065] The type of polyamide resin used as the laser absorbing resin is not particularly limited, and may be any polyamide resin other than the semi-aromatic polyamide material disclosed herein.

[0066] Useful lasers for welding the molded resin products of the present invention may be any laser having light emission in the near infrared region. In particular, lasers emitting light with a wavelength of 800-1200 nm are preferred, with diode lasers and YAG lasers being particularly preferred. The lasers may be used alone or in combination with one another, as will be understood by those skilled in the art of laser operation. The laser emission may be continuous or pulsed, with continuous emission being preferred.

[0067] The intensity, density and irradiation area of ​​the laser are selected to appropriately heat and melt the joining surfaces. These are adjusted in such a way as to obtain a bond that has the strength required for the application of interest. If it is too weak, sufficient heating and melting cannot be achieved. On the contrary, if it is too strong, it may cause degradation of the resin.

[0068] The present invention relates to a joining portion of two molded products (laser-transmitting and laser-absorbing, respectively) placed in contact with each other, wherein a predetermined amount of laser beam is focused and transmitted, melting and bonding the joining portion. If multiple points, lines or surfaces are to be welded, the laser can be moved sequentially to irradiate the joining surface, or multiple laser sources can be used to irradiate simultaneously.

[0069] The laser welding parts disclosed in the present invention can be semi-finished products, finished products, or a component that forms them. Different from traditional connection methods, the laser welding parts of the present invention have high mechanical properties, flame retardancy, solvent resistance, bonding strength, less or no post-processing, and no obvious thermal or mechanical damage. It can be applied to components with coolant resistance and flame retardancy requirements in new energy vehicle battery systems and thermal management systems, such as electronic water pumps, electronic cooling pipe joints, and 12V battery boxes.

[0070] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0071] The first polyamide:

[0072] PA6T / 6I-1 is homemade, and its preparation method is as follows:

[0073] Hexamethylenediamine, dicarboxylic acid, benzoic acid and deionized water are added into a reactor with a nitrogen atmosphere and a pressure of 2.8 MPa, the reactor is heated to 180°C for reaction for 1 hour, and then the temperature is continued to be raised to 235°C for reaction for 12 hours to obtain PA6T / 6I-1; wherein the dicarboxylic acid is terephthalic acid and isophthalic acid, and the total molar content of the dicarboxylic acid is 100%, the molar content of terephthalic acid is 70%, and the molar content of isophthalic acid is 30%; the ratio of the total molar content of the dicarboxylic acid to the molar content of hexamethylenediamine is 1:1, and the molar content of benzoic acid is 1% of the total molar content of the dicarboxylic acid.

[0074] PA6T / 6I-2 is homemade, and its preparation method is different from that of PA6T / 6I-1 only in that the molar content of terephthalic acid is 65%, the molar content of isophthalic acid is 35%, and the rest are the same.

[0075] PA6T / 6I-3 is homemade, and its preparation method is different from that of PA6T / 6I-1 only in that the molar content of terephthalic acid is 60%, the molar content of isophthalic acid is 40%, and the rest are the same.

[0076] PA6T / 6I-4 is homemade, and its preparation method is different from that of PA6T / 6I-1 only in that the molar content of terephthalic acid is 80%, the molar content of isophthalic acid is 20%, and the rest are the same.

[0077] PA6T / 6I-5 is homemade, and its preparation method is different from that of PA6T / 6I-1 only in that the molar content of terephthalic acid is 50%, the molar content of isophthalic acid is 50%, and the rest are the same.

[0078] Second polyamide:

[0079] PA6I / 6T-1 is homemade, and its preparation method is different from PA6T / 6I-1 only in that the molar content of terephthalic acid is 30%, the molar content of isophthalic acid is 70%, and the rest are the same.

[0080] PA6I / 6T-2 is homemade, and its preparation method is different from that of PA6T / 6I-1 only in that the molar content of terephthalic acid is 35%, the molar content of isophthalic acid is 65%, and the rest are the same.

[0081] PA6I / 6T-3 is homemade, and its preparation method is different from that of PA6T / 6I-1 only in that the molar content of terephthalic acid is 40%, the molar content of isophthalic acid is 60%, and the rest are the same.

[0082] Flame retardant: aluminum diethylphosphinate, Clariant;

[0083] Filler: glass fiber, ECS301HP, average length 3 mm, Chongqing International Composite Materials Co., Ltd.

[0084] Polyvinylpyrrolidone: PVP K25, Huzhou Shenhua Polymer;

[0085] PA66: U4800, Shenma.

[0086] Examples and Comparative Examples

[0087] The components and weight proportions of the semi-aromatic polyamide materials of the embodiment and the comparative example are shown in Table 1 and Table 2, wherein the preparation method of the semi-aromatic polyamide materials of the embodiment and the comparative example comprises the following steps:

[0088] According to Table 1 and Table 2, the first polyamide, the second polyamide and polyvinyl pyrrolidone are uniformly mixed, and the obtained mixture is added to the main feeding system of the extruder for melt mixing, the flame retardant is added to the first side feeding system of the extruder, and the glass fiber is added to the second side feeding system of the extruder, and the mixture is extruded and granulated to obtain a semi-aromatic polyamide material; wherein the aspect ratio of the twin-screw extruder is 52:1, the screw speed is 200rpm, the extrusion temperature is 290-340°C, and the feeding rate is 350kg / h.

[0089] The semi-aromatic polyamide materials obtained in the examples and comparative examples were subjected to performance tests, and the test methods were as follows:

[0090] (1) Coolant retention rate: In accordance with ISO 527-1 / -2, a semi-aromatic polyamide material is injection molded into a standard tensile specimen and a strength test is performed in accordance with the standard. This is the initial tensile strength A1. The tensile specimen is then placed in an ethylene glycol / water solution with a volume ratio of ethylene glycol to water of 1:1. The specimen is placed in a sealed container at 150°C for 96 hours. The tensile specimen is taken out and a tensile strength test is performed in accordance with ISO527-1 / -2. This is the tensile strength A2 after being immersed in the coolant. A2 / A1 is the coolant retention rate.

[0091] (2) Light transmittance: The semi-aromatic polyamide material was injection molded into a 100 mm*100 mm*2 mm square plate, and the light transmittance at 960 mm was tested using a light transmittance tester;

[0092] (3) Flame retardancy: Referring to the UL94 V-0 test standard, the semi-aromatic polyamide material was injection molded into standard strip specimens with a length of 125±5 mm, a width of 13.0±0.5 mm, and a thickness of 3.0 mm. Five standard strip specimens were placed at a temperature of 23°C and a humidity of 50% for 48 h.

[0093] Aim the flame of the Bunsen burner at the center of the lower end of the sample, and keep the distance between the center of the top surface of the Bunsen burner tube and the lower end surface of the sample at 10±1mm, and keep this distance for 10±0.5S: if necessary, the Bunsen burner can be moved according to the change of the length and position of the sample. After applying the flame to the sample for 10±0.5S, immediately withdraw the Bunsen burner at a rate of about 300mm / s to at least 150mm away from the sample. At the same time, use a timing device to measure the flame burning time T1 (in seconds) of the sample. After the flame burning of the sample stops, even if the Bunsen burner is not withdrawn from the sample by 150mm, immediately move the Bunsen burner to the lower end surface of the sample and keep the distance at 10±1mm, and apply the flame again for 10±0.5S. If necessary, move the Bunsen burner away to clean up drippings. After applying the flame, immediately withdraw the Bunsen burner away from the sample by at least 150mm, and start the timing device to measure the flame burning time T2 and the flameless burning time T3 of the sample, and record T2 and T3. If T1+T2+T3 of the five specimens are all less than 10s, and there is no dripping to ignite the cotton below, the V-0 condition is considered to be met.

[0094] (4) Laser welding strength: The semi-aromatic polyamide material was injection molded into a 50 mm*50 mm*2 mm square plate and welded at a wavelength of 960 mm, a welding speed of 500 mm / s, a welding pressure of 3 bar, a welding time of 2 s, and a welding power of 80 W to obtain a welded sample. The welded sample was subjected to a destructive force test using the ISO 527-1 / -2 method to obtain the laser welding strength.

[0095] The test results are shown in Table 1 and Table 2.

[0096] Table 1

[0097]

[0098]

[0099] Table 2

[0100]

[0101]

[0102] From the experimental data in Tables 1 and 2, it can be seen that the coolant retention rate of the semi-aromatic polyamide material disclosed in the present invention is 69.5-83.1%, the flame retardancy is V-0, the light transmittance is 35.2-45.3%, and the laser welding strength is 1528-2098N, indicating that the semi-aromatic polyamide material disclosed in the present invention has high solvent resistance, flame retardancy, light transmittance and laser welding strength.

[0103] By comparing Example 1, Examples 3-4 and Comparative Examples 1-2, it can be seen that, based on the total molar content of the dicarboxylic acid as 100%, the molar content of terephthalic acid in the first polyamide is 60-70%, and the obtained semi-aromatic polyamide material has a coolant retention rate of 69.5-80.3%, a flame retardancy of V-0, a light transmittance of 39.5-44.3%, and a laser welding strength of 1833-1995N; it indicates that the obtained semi-aromatic polyamide material has high solvent resistance, flame retardancy, light transmittance and laser welding strength.

[0104] It can be seen from Comparative Examples 1 and 3 that when PA66 is used as the first polyamide, the coolant retention rate of the obtained semi-aromatic polyamide material is 30.3%, and the flame retardancy is V-2, indicating that using PA66 as the first polyamide will lead to a decrease in the solvent resistance and flame retardancy of the semi-aromatic polyamide material.

[0105] It can be seen from Comparative Examples 1, Examples 7-9 and Comparative Examples 5-6 that the weight of the second polyamide is 5-10 parts, and the coolant retention rate of the obtained semi-aromatic polyamide material is 70.4-83.1%, the flame retardancy is V-0, the light transmittance is 35.3-45.3%, and the laser welding strength is 1528-2098N; the weight of the second polyamide is 6.5-8 parts, and the coolant retention rate of the obtained semi-aromatic polyamide material is 80.3-83.1%, the flame retardancy is V-0, the light transmittance is 36.2-39.5%, and the laser welding strength is 1621-1833N, indicating that when the weight of the second polyamide is 6.5-8 parts, the solvent resistance, flame retardancy, light transmittance and laser welding strength of the obtained semi-aromatic polyamide material are higher.

[0106] By comparing Example 1 and Comparative Example 7, it can be seen that in the absence of polyvinyl pyrrolidone, the transmittance of the obtained semi-aromatic polyamide material is 30%, and the laser welding strength is 1000N, indicating that the lack of polyvinyl pyrrolidone will lead to a significant decrease in the transmittance and laser welding strength of the semi-aromatic polyamide material.

[0107] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present disclosure rather than to limit the protection scope of the present disclosure. Although the present disclosure has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present disclosure can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present disclosure.

Claims

1. A semi-aromatic polyamide material, characterized in that: The invention comprises the following components in parts by weight: 45-62 parts of a first polyamide, 5-10 parts of a second polyamide, 3-5 parts of polyvinyl pyrrolidone, 10-12 parts of a flame retardant, and 20-30 parts of a filler; Wherein, the first polyamide and the second polyamide are copolymers of dicarboxylic acid and hexamethylenediamine, and the dicarboxylic acid is terephthalic acid and isophthalic acid; The first polyamide comprises repeating units derived from 60-70% terephthalic acid and 30-40% isophthalic acid, based on 100% of the total molar content of dicarboxylic acids; the second polyamide comprises repeating units derived from 30-40% terephthalic acid and 60-70% isophthalic acid.

2. The semi-aromatic polyamide material according to claim 1, characterized in that The molar content of terephthalic acid in the first polyamide is 65-70%.

3. The semi-aromatic polyamide material according to claim 1, characterized in that The weight portion of the second polyamide is 6.5-8 parts.

4. The semi-aromatic polyamide material according to claim 1, characterized in that The flame retardant is aluminum diethylphosphinate.

5. The semi-aromatic polyamide material according to claim 1, characterized in that The filler is at least one of a fibrous filler and a non-fibrous filler; the fibrous filler is selected from at least one of glass fiber, carbon fiber, and organic fiber, and the non-fibrous filler is selected from at least one of a granular filler, a layered filler, and a nano filler.

6. The semi-aromatic polyamide material according to claim 1, characterized in that The semi-aromatic polyamide material further comprises 1-3 parts by weight of a processing aid; the processing aid comprises at least one of a heat stabilizer, an antioxidant, a nucleating agent, an antistatic agent, a foaming agent, a lubricant, a plasticizer, a release agent, and a pigment.

7. A method for preparing a semi-aromatic polyamide material according to any one of claims 1 to 6, characterized in that: The following steps are involved: After each component is uniformly mixed according to a certain proportion, it is melt-extruded and granulated to obtain a semi-aromatic polyamide material.

8. The method for preparing a semi-aromatic polyamide material according to claim 7, characterized in that: The temperature of the melt extrusion granulation is 290-340°C.

9. Use of the semi-aromatic polyamide material according to any one of claims 1 to 6 in the preparation of laser welding parts.

10. A laser welding component, characterized in that: The laser welding component comprises the semi-aromatic polyamide material according to any one of claims 1-6.

Citation Information

Patent Citations

  • Flowable polyamides

    CN105504800A

  • Polyamide resin composite material, and preparation method and application thereof

    CN106633858A

  • Impact-resistant polyamide compositions

    EP0885930A1